2018
DOI: 10.1039/c8bm00317c
|View full text |Cite|
|
Sign up to set email alerts
|

The role ofSox9in collagen hydrogel-mediated chondrogenic differentiation of adult mesenchymal stem cells (MSCs)

Abstract: Sox9 is a transcription factor that regulates chondrogenesis, but its role in the chondrogenic differentiation of mesenchymal stem cells (MSCs) triggered by materials is poorly understood. In this study, we investigated the effect of Sox9 interference on collagen-induced chondrogenesis and further collagen-based therapies for cartilage defects. In this paper, MSCs were infected with a vector carrying the Sox9 promoter and related markers were detected. A lentivirus-mediated vector targeting the silencing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…In the chondrogenic commitment of human MSCs, the transcription factorSox9 plays a key role and is considered as an early chondrogenic marker; its upregulation drives the correct chondrogenic phenotype, decreasing the hypertrophic drift of the cells (Jiang et al, 2018) which would gradually promote mineralization of hyaline cartilage and result in apoptosis and ossification (Mueller and Tuan, 2008). At day 16, supplementing 1 ng/mL of hTGFβ1, Sox9 levels doubled ( Figure 1a ); whereas, using 10 ng/mL, Sox9 showed a fourfold up-regulation ( Figure 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…In the chondrogenic commitment of human MSCs, the transcription factorSox9 plays a key role and is considered as an early chondrogenic marker; its upregulation drives the correct chondrogenic phenotype, decreasing the hypertrophic drift of the cells (Jiang et al, 2018) which would gradually promote mineralization of hyaline cartilage and result in apoptosis and ossification (Mueller and Tuan, 2008). At day 16, supplementing 1 ng/mL of hTGFβ1, Sox9 levels doubled ( Figure 1a ); whereas, using 10 ng/mL, Sox9 showed a fourfold up-regulation ( Figure 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…In a minipig study colonization of the cell free Col matrix gave outcome comparable to matrix assisted chondrocyte implantation [48,49]. Jiang et al demonstrated superior chondrogenic differentiation of MSC embedded in Col compared to MSC only in a rat model [50]. On the other hand, HA has been combined with Col 1 or gelatin before with similar outcomes that chondrogenic differentiation is promoted in the composite compared to HA or Col only [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…By using type I collagen as scaffold combined with stromal cell-derived factors-1 (SDF-1) as growth factor, Zhang et al successfully induced the migration and adhesion of C-MSCs and SM-MSCs and promoted the self-repair of partial thickness defects [ 30 ]. Another study conducted by Jiang et al indicated that collagen-based hydrogel encapsulated with MSCs could mediate the expression of Sox9 (a transcription factor regulates chondrogenesis), suggesting that appropriately designed hydrogel scaffold may work without growth factor [ 101 ]. Collagen can also be combined with other materials to form hybrid hydrogel scaffolds that have enhanced properties compared to the individual components.…”
Section: Current State-of-art Of Hydrogels Designed For Cartilage Regmentioning
confidence: 99%